2016
DOI: 10.1128/mbio.00836-16
|View full text |Cite
|
Sign up to set email alerts
|

The Core and Seasonal Microbiota of Raw Bovine Milk in Tanker Trucks and the Impact of Transfer to a Milk Processing Facility

Abstract: Currently, the bacterial composition of raw milk in tanker trucks and the outcomes of transfer and storage of that milk at commercial processing facilities are not well understood. We set out to identify the bacteria in raw milk collected for large-scale dairy product manufacturing. Raw bovine milk samples from 899 tanker trucks arriving at two dairy processors in San Joaquin Valley of California during three seasons (spring, summer, and fall) were analyzed by community 16S rRNA gene sequencing. This analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
122
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 85 publications
17
122
0
2
Order By: Relevance
“…Streptococcus was the most abundant bacterial genus in the milk on both sampling dates, as was previously observed for raw milk in tanker trucks delivered to the same facility (20). Because this genus was consistently found in milk from all pieces of equipment, including among the viable cells measured after pasteurization, our findings support the work of others showing the persistence of this genus in milk during the manufacture of cheese and other dairy products (13,23).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Streptococcus was the most abundant bacterial genus in the milk on both sampling dates, as was previously observed for raw milk in tanker trucks delivered to the same facility (20). Because this genus was consistently found in milk from all pieces of equipment, including among the viable cells measured after pasteurization, our findings support the work of others showing the persistence of this genus in milk during the manufacture of cheese and other dairy products (13,23).…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported that milk produced and transported in tanker trucks in central California contains a highly diverse assemblage of bacteria that is subject to modification over relatively short periods of time in storage silos at dairy processing facilities (20). Here, we characterized the bacterial diversity in milk as it passes through different processing stages at a large-scale dairy facility prior to the final pasteurization step used in cheese manufacture.…”
mentioning
confidence: 99%
“…In this study, the less prevalent genera in goat milk constituted a significant proportion of the total bacterial population; this result is similar to results published in other reports (Kable et al, 2016; Quigley et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The 16S rRNA V4 region was amplified as previously described [31] using primers F515 and R806 [32]. A unique eight nucleotide Hamming code sequence was included on the 5’ end of F515 [33, 34] for amplification of each sample.…”
Section: Methodsmentioning
confidence: 99%